Book Review: Jannel, R. Yamauchi Tokuryū (1890–1982). Philosophie occidentale et pensée bouddhique; Éditions Kimé: Paris, France, 2023; ISBN: 978-2-38072-114-0 - Joseph E. Brenner (Philosophies, 2024)
A recent book by Romaric Jannel on the work of the 20th Century Japanese philosopher Yamauchi Tokuryū is reviewed as a prolegomenon in this journal to more detailed studies of Oriental philosophy. Emphasis is placed on the similarities and overlaps of Eastern and Western thought.